Does Cancer Therapy Causes Cancer? A Case Report and Mini Review of the Literature - Nikolaos Thomakos; Alexandros Rodolakis; Nikolaos Akrivos; Pantelis Palaiologos; Dimitrios Haidopoulos; Georgios Vlahos; Aris Antsaklis (Medical Network, 2010)
The subject of whether cancer treatment causes cancer is less widely recognized but obviously not insignificant. Although previous studies have attempted to address the concept of "postradiation carcinoma" there is no direct evidence that these tumors are caused by radiation or simply present incident malignancies in an at-risk population. The risk of second primary cancer in women with cervical cancer in previously irradiated fields remains still unclear. We present an atypical case of endometrial cancer formerly submitted to pelvic irradiation because of cervical carcinoma and we discuss the eventual association of pelvic radiation with a subsequent endometrial carcinoma.